Dong Thap university journal of science: Natural sciences issue (Dong Thap University, 2022)
Content: Error bounds for a class of mixed parametric vector quasi-equilibrium problems, A unified approach to zero duality gap for convex optimization problems, Drinfel'd associator and relations of some special functions,...